Analysis of the disease activity of ulcerative colitis with and without concomitant primary sclerosing cholangitis: An investigation using a nationwide database in Japan. Issue 1 (28th December 2021) - Yano, Kota; Moroi, Rintaro; Shiga, Hisashi; Tarasawa, Kunio; Shimoyama, Yusuke; Kuroha, Masatake; Hamada, Shin; Kakuta, Yoichi; Fushimi, Kiyohide; Fujimori, Kenji; Kinouchi, Yoshitaka; Masamune, Atsushi
Abstract: Aims: Primary sclerosing cholangitis (PSC) is a relatively common complication of ulcerative colitis (UC). Only a few studies have investigated the impact of PSC on the clinical course of UC, and their conclusions are contradictory. Therefore, we aimed to compare the disease activity of UC with and without PSC. Methods and Results: We collected UC patient data using the Diagnosis Procedure Combination database system in Japan and classified eligible admissions into two groups based on their diagnosis of either UC alone or UC associated with PSC. We then compared therapeutic details (medical treatment and surgery) between the two groups. Multivariable logistic regression analysis and propensity score matching was also performed. The rates of systemic steroid injection and infliximab administration in patients with PSC were lower than those in patients without PSC (21% vs. 28%, P = 0.012, 9.6% vs. 16%, P = 0.01, respectively). The rates of surgery, colorectal cancer, duration of hospital stay, and in‐hospital mortality did not differ between the two groups. Multivariable analysis revealed that concomitant PSC was a clinical factor that reduced the odds of systemic steroid injection (odds ratio [OR] = 0.66, 95% confidence interval [CI]: 0.49–0.90, P = 0.008) and infliximab (OR = 0.48, 95% CI: 0.32–0.74, P = 0.0008) administration. Conclusion: UC patients with PSC might have less UC disease activity than those with UC alone. Abstract : We compared ulcerative colitis alone (UC) and UC‐associated primary sclerosing cholangitis (UC‐PSC) using a nationwide database in Japan. The propensity score‐matched analysis revealed that the rates of administration of systemic steroid and infliximab in the UC‐PSC group were lower than that of the UC group. Our results indicate that UC‐PSC patients might have lesser disease activity compared to UC patients.